ANALISIS POTENSI BAHAYA KERJA DAN PENGENDALIANNYA PADA STASIUN LOADING RAMP DI PABRIK PENGOLAHAN KELAPA SAWIT DENGAN METODE HIRAC: Analisis Potensi Bahaya dalam Kerja - wesila (Jurnal Teknologi Infrastruktur, 2023)
ABSTRACT Analysis of Potential Occupational Hazards and Their Control at Loading Ramp Station in Palm Oil Processing Plant with HIRAC Method PT Pundi Lahan Khatulistiwa is a limited liability company engaged in the plantation business and palm oil processing. Based on data on work accidents in the palm oil processing process of PT Pundi Lahan Khatulistiwa Kubu Raya Regency from 8 stations, the number of work accident cases from 2014-2021 was obtained, namely at the granding station there were 2 cases, the loading ramp station had 5 cases, the sterilizer station had 1 case, the digester and press station had 3 cases, the clarification station had 1 case, the nut and kerrel station had 2 cases, the boiler station had 2 cases, and the engine room station had 1 case. Based on this data, the researchers analyzed the potential hazards and controls at the loading ramp station which will be carried out using the HIRAC method. This study aims to determine the potential hazards that exist, conduct risk assessment and control. The data collection method used a hazard identification sheet and interviews with loading ramp station workers. The result of this research is that the potential hazard value for the medium risk category is 45%, high risk is 45% and extreme risk is 10%. From the potential hazards that have been obtained, hierarchy controls are carried out on the source of danger so that the risk level of extreme and high categories becomes medium by 45%, and the medium category becomes low by 55%. Keywords: HIRAC, Loading Ramp, Potential Hazards, Risk Assessment, Station